Severity and treatment level of acute gastroenteritis with rotavirus in children under 5 years in INDONESIA - Fatma Othman Gdara; Jarir At Thobari; Yati Soenarto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Rotavirus diarrhea causing gastroenteritis in children under five years is an importantissue that urgently needs to be addressed globally. Delay in management of rotavirusdiarrhea can be fatal. Diagnostic tool for detecting rotavirus is, therefore, needed.However, until now the gold standard diagnostic tools are expensive, often not availableand affordable in health care settings. The aim of the study was to compare the Vesikariclinical severity score of rotavirus-positive with rotavirus-negative in hospitalized childrenwith acute gastroenteritis. Furthermore, the difference of the level of treatment betweenrotavirus-positive with rotavirus-negative was also evaluated. This was a cross sectionalstudy that using secondary data from medical records of five general teaching hospital inIndonesia. Subjects were children aged <5 years with acute watery diarrhea admitted tothe hospital. Statistical analysis used was chi square test, U-Mann Whitney, and KruskalWallis. The results showed that the patient with rotavirus positive have higher dehydration(80.2%) compared to rotavirus negative (70%). The severity level of clinical feature washigher in diarrhea due to rotavirus positive than non rotavirus (11.47± 2.89 vs 10.41± 2.70; p<0.000). The level of treatment was higher in rotavirus positive. The majorityhad treatment plan C (47.7%) higher than plan B and A (45.6% and 30.9%; p<0.050).This was opposite with patient with rotavirus negative that majority had treatment inplan A (69.1%) higher than plan B and C (54.4% and 52.3%) (p<0.001). In conclusion,the severity of gastroentrities in children under 5 years using vesikari score are higher indiarrhea due to rotavirus positive than non rotavirus. The treatment level plan C is higherthan plan B and A in diarrhea due to rotavirus. This is opposite with non rotavirus majorityhave treatment in plan A higher than plan B and C.